International Cooperation for Enhancing Nuclear Safety, Security, Safeguards and Non-proliferation-60 Years of IAEA and EURATOM: Proceedings of the XX Edoardo Amaldi Conference, Accademia Nazionale dei Lincei, Rome, Italy, October 9-10, 2017 - Maiani, Luciano; Abousahl, Said; Plastino, Wolfango (Springer Proceedings in Physics, 2018)
EU Member State on the Evolution of Nuclear Safety; EU Perspective on Nuclear Safety; IAEA Nuclear Safeguards; Nuclear Energy in the Amaldi Conference; Nuclear Non-proliferation; Nuclear Safeguards; Nuclear Security; Role of Scientific Community for Nuclear Safety; Scientists for Global Security; Nuclear Safety; Nuclear Disarmament